Large increase in the energy product of Fe3Se4 by Fe-site doping - Sen Bishwas, Mousumi; Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Fe3Se4 possesses a large coercivity at room temperature. At lower temperature, a coercivity value up to 40 kOe has been achieved. However, due to a relatively lower saturation magnetization value, the energy product of this material is not suitable for its use as rare-earth-free hard magnetic material. Although the anisotropy and magnetic structure of Fe3Se4 have been topics of research, there is no attempt to increase the energy product. Here, we report the synthesis of Fe3-xMnxSe4 (x = 0.01-0.2) nanorods. As required for practical applications, after doping, the Curie temperature remains unchanged; however, at optimum (x = 0.03) doping of manganese ions, the magnetization of the host matrix increases significantly from 4.84 to 7.54 emu/g. The corresponding energy product value was found to be increased by more than 130%. At low temperature (10 K) the energy product shows almost a 2 order of magnitude increase (similar to 0.12 MG Oe), which makes it valuable for many low temperature applications. This improvement is a vital step for its use in some of the household applications where a large volume and relatively lower energy product are needed.